Sintesis dan Karakterisasi Senyawa 4'-Aminokalkon dengan Metode Pengadukan dan Refluks Termodifikasi - Rahma Dona; Enda Mora; Nurul Huda (LPPM Universitas Abdurrab, 2025)
Chalcone is a secondary metabolite belonging to the minor group of flavonoids which has various biological activities. Several chalcone derivatives with amino groups attached to their rings have anti-inflammatory, antibacterial, antitumor and antimalarial activities. However, because the amount is limited, the percentage in plants is small, and the structural variations are relatively small, it needs to be synthesized in the laboratory. This study aims to compare the results of the synthesis of 4'-aminochalcone compounds using the stirrer method at room temperature and modified reflux at an increased temperature. Synthesis using the stirrer method was carried out for 4 hours at room temperature with NaOH 40% as catalyst, while synthesis using the modified reflux method was carried out using a monowave-50 for 11 minutes at a temperature of 80oC with the same catalyst. The molecular structures of the synthesized compound were confirmed by UV spectroscopy, FT-IR, and 1H-NMR spectral data. Based on this study results, it was found that the synthesis of 4'-aminochalcone compounds using the stirrer method had better results compared to the modified reflux method. The 4'-aminochalcone compound using the stirrer method had a pure compound yield of 47.36%, while the 4'-aminochalcone compound using the modified reflux method had an impure yield of 2.57%. Characterization using UV spectroscopy, FT-IR, and 1H-NMR shows that the synthesis results match the structure of the target molecule.